Simultaneous inhibition of ATR and PARP sensitizes colon cancer cell lines to irinotecan - Abu-Sanad, Atlal; Wang, Yunzhe; Hasheminasab, Fatemeh; Panasci, Justin; Noe, Alycia; Rosca, Lorena; Davidson, David; Sharif-Askari, Bahram; Amrein, Lilian; Aloyz, Raquel; Panasci, Lawrence (Frontiers in Pharmacology, 2015)
Enhanced DNA damage repair is one mechanism involved in colon cancer drug resistance. Thus, targeting molecular components of repair pathways with specific small molecule inhibitors may improve the efficacy of chemotherapy. ABT-888 and VE-821, inhibitors of poly-ADP-ribose-polymerase (PARP) and the serine/threonine-kinase Ataxia telangiectasia related (ATR), respectively, were used to treat colon cancer cell lines in combination with the topoisomerase-I inhibitor irinotecan (SN38). Our findings show that each of these DNA repair inhibitors utilized alone at nontoxic single agent concentrations resulted in sensitization to SN38 producing a 1.4 to 3 fold reduction in the 50% inhibitory concentration (IC50) of SN38 in three colon cancer cell lines. When combined together, nontoxic concentrations of ABT-888 and VE-821 produced a 4.5 to 27 fold reduction in the IC50 of SN38 with the HCT-116 colon cancer cells demonstrating the highest sensitization as compared to LoVo and HT-29 colon cancer cells. Furthermore, the combination of all three agents was associated with maximal G2-M arrest and enhanced DNA-damage (γH2AX) in all three colon cancer cell lines. The mechanism of this enhanced sensitization was associated with: (a) maximal suppression of SN38 induced PARP activity in the presence of both inhibitors and (b) ABT-888 producing partial abrogation of the VE-821 enhancement of SN38 induced DNA-PK phosphorylation, resulting in more unrepaired DNA damage; these alterations were only present in the HCT-116 cells which have reduced levels of ATM. This novel combination of DNA repair inhibitors may be useful to enhance the activity of DNA damaging chemotherapies such as irinotecan and help produce sensitization to this drug in colon cancer.